(untitled) (REMUNOM, 2025)
Despite the existence of several systems related to sustainability assessment, there are several elements that are not yet properly studied and developed. In the context of sustainable finance and its sustainability indicators, this research carries out a comparative analysis of the following corporate sustainability indices: Dow Jones Index (DJI), Dow Jones Sustainability Indexes (DJSI), FTSE 100, FTSE4FGOOD Global Index, IBOVESPA and the Corporate Sustainability Index (ISE). As main results it was identified that the series of returns of the sustainability indices, in the long term, oscillate around an average seeking a statistical balance. In addition, when evaluating the comparison between the indices of the same market, through the same profitability parameter, to a risk-free scenario, it was concluded that there is a better performance for the indices constituted by companies that guide its actions and businesses in sustainability.